TAXONOMIA E FILOGENIA DE Urera (URTICACEAE) OCORRENTES NO BIOMA MATA ATLÂNTICA - Suchoronczek, Andreia (2019)
Urera Gaudich. is inserted into the tribe Urticeae Lam. & DC. of Urticaceae Juss., has about 35 species, six of which occur in Brazil. The genus is characterized by subshrubs, shrubs, small trees and creepers with presence of urticating trichomes on branches and leaves; inflorescences at the cymes or glomeruli and staminate flowers with 4-5 tepals, 4-5 stamens, pistillate with 4 tepals; achenes surrounded by fleshy perigones. This genus does not have recent taxonomic revisions and studies for the Atlantic Forest are scarce and it diversity lacks of knowledge. The Atlantic Forest is one of the biomes considered hotspots, because it presents great diversity and many endemic species that are under high threat. Thus, the aim of this study were: to elaborate a taxonomic synopsis of Urera with focus in the species occurring in the Atlantic Forest biome; to test the monophyly of Urera and to position its species phylogenetically. The taxonomic treatment was based on the analysis of 1654 materials from brazilian and foreign herbarium, with physical visits or virtual platforms, including type materials, and observation of populations in nature. In addition, reference work was consulted for the group. For the phylogenetic analyzes, samples of Urera occurring in the Atlantic Forest biome were sequenced using chloroplastid (psbA-trnH, trnL-trnF) and nuclear (ITS 4-5) markers. The phylogenetic tree was created with the 09 acessions obtained in this study, in addition to 53 accessions obtained from GenBank. Four species were identified for the Atlantic Forest biome: Urera aurantiaca Wedd., U. baccifera (L.) Gaudich. ex Wedd., U. caracasana (Jacq.) Griseb. and U. nitida (Vell.) P. Brack. Descriptions, identification keys, comments on taxonomy, ecological observations and geographic distribution for the species are presented. The phylogeny of the group showed Urera as a paraphyletic clade, with the species occurring in the Atlantic Forest close to other species of the Neotropical and Afrotropical regions. The monophyly of a clade formed by species with occurrence for the Atlantic Forest biome does not support our analyzes, due to the phylogenetic position of Urera aurantiaca and U. caracasana. The analyzes also indicate that Laportea is a paraphyletic genus, whereas, the genera Obetia and Poikilospermum are monophyletic. The present study represents the most detailed molecular phylogenetic information of Urera available until the date, and illustrates the need to investigate this group more deeply.